High-Temperature Tensile Fractography of Zr-, Ni-, and Mn-Containing Al-Si-Cu-Mg Cast Alloys - M. H. Abdelaziz; E. M. Elgallad; A. M. Samuel; H. W. Doty; F. H. Samuel (Advances in Materials Science and Engineering)
This study investigated the fracture behavior of 0.3% Zr-containing 354 alloy following the addition of 0.75% Mn or 2%Ni. The examined surfaces were obtained from tensile testing of the bars at 250°C. For each alloy, the test bar samples were examined in the T6-treated conditions after being exposed to 250°C for 1 and 200 hours. The fracture surface of the base alloy (0.3% Zr-containing 354 alloy) after stabilization for one hour at 250°C reveals a dimpled structure throughout, indicating the ductile nature of the fracture mode. The Alx (Zr, Ti)Si complex compound is observed with star-like and blocky morphologies, with cracks appearing in various particles of this compound. By increasing the stabilization time up to 200 hours, coarser and deeper dimples are formed, highlighting the increased ductility of the alloy due to the softening behavior associated with the prolonged exposure at 250°C. In the one-hour stabilized T6-treated condition alloy containing 2% Ni tested at 250°C, the appearance of microcracks in the Ni-rich phases and the lower density of dimples on the fracture surface compared to those observed in the base alloy emphasize the low ductility of alloy due to Ni-containing intermetallics. Examination of the fracture surface of Mn-containing alloys revealed the advantageous role of sludge particles in resisting the propagation of cracks that developed in many intermetallic phases.